MEDIATION IN THE CONTEXT OF THE EDUCATIONAL ACTIVITY OF THE MODERN MUSEUM - Yuliia Kliuchko (Культура і мистецтво у сучасному світі)
The purpose of this article is to reveal and generalise the essence of museum mediation under the conditions of modern museum space; to examine the mediation as a form of educational activity of the museum. The research methodology involves the use of such methods as analysis, systematisation and generalisation to identify the concept of museum mediation in the context of the educational activity of the museum institution. Taking into account the current state of museum studies in Ukraine where mediation as a form of educational activity is on the initial stage of development in museums and museum-type institutions, this research systematises and generalises the basic theoretical achievements; it is demonstrated that at the present stage the topic of research has not yet been comprehensively displayed in the national scientific literature. The mediation is defined and characterized as an innovative form of educational activity in museums in Ukraine. Conclusions. It has been found that today for the museum as one of the centres of communication in the cultural space the important result of its activity is the establishment of the stable and constructive dialogue with its audience. It is determined that modern museology regards the mediation as a specific form of communication at the intersection of the main directions of activity: scientific-stock, research, exposition and education. The study has confirmed that a field for positive understanding of the parties (exposition space, museum expert, visitor), for search of the new options acceptable for all participants of communication is created in the process of museum mediation. Mediation as a form of educational activity of the museum facilitates the mobilization of different methods, means and technologies for updating a museum item and presenting it to a visitor. The result is the formation of personal attitude towards the historical context, which can inspire the process of self-knowledge and give the reason to consider the museum as a unique cultural institution where through mediation self-knowledge and cognition of the surrounding reality are realised. The expediency of introducing mediation as a form of educational activity in domestic museums is justified.